Assessment of different classification systems for predicting the risk of superior laryngeal nerve injury during thyroid surgery: a prospective cohort study - Li, Changlin; Zhang, Jiao; Dionigi, Gianlorenzo; Sun, Hui (Frontiers in Endocrinology, 2023)
Background A multitude of anatomical variations have been noted in the external branch of the superior laryngeal nerve (EBSLN). In this study, intraoperative neuromonitoring (IONM) was used to assess the potential value of the different classical EBSLN classifications for predicting the risk of EBSLN injury. Methods In total, 136 patients with thyroid nodules were included in this prospective cohort study, covering 242 nerves at risk (NAR). The EBSLN was identified by observing the cricothyroid muscle twitch and/or typical electromyography (EMG) biphasic waveform. The EBSLNs were classified by Cernea classification, Kierner classification, and Friedman classification, respectively. The EMG parameters and outcomes of vocal acoustic assessment were recorded. Results The distribution of Cernea, Kiernea, and Friedman subtypes were, respectively, Cernea 1 (40.9%), Cernea 2A (45.5%), Cernea 2B (10.7%), Kierner 1 (40.9%), Kierner 2 (45.5%), Kierner 3 (10.7%), Kierner 4 (2.9%) and Friedman 1 (15.7%), Friedman 2 (33.9%), Friedman 3 (50.4%). The amplitudes of EBSLN decreased significantly after superior thyroid pole operation, respectively, in Cernea 2A (193.7 vs. 226.6μV, P=0.019), Cernea 2B (185.8 vs. 221.3μV, P=0.039), Kierner 2 (193.7vs. 226.6μV, P=0.019), Kierner 3 (185.8 vs. 221.3μV, P=0.039), Kierner 4 (126.8vs. 226.0μV, P=0.015) and Friedman type 2 (184.8 vs. 221.6μV, P=0.030). There were significant differences in Fmax and Frange for Cernea 2A (P=0.001, P=0.001), 2B (P=0.001, P=0.038), Kierner 2 (P=0.001), Kierner 3 (P=0.001, P=0.038), and Friedman 2 (P=0.004, P=0.014). In the predictive efficacy of EBSLN injury, the Friedman classification showed higher accuracy (69.8% vs. 44.3% vs. 45.0%), sensitivity (19.5% vs. 11.0% vs. 14.0%), and specificity (95.6% vs. 89.9% vs. 89.9%) than the Cernea and Kierner classifications. However, the false negative rate of Friedman classification was significantly higher than other subtypes (19.5% vs. 11.0% vs. 14.0%). Conclusion Cernea 2A and 2B; Kierner 2, 3, and 4; and Friedman 2 were defined as the high-risk subtypes of EBSLN. The risk prediction ability of the Friedman classification was found to be superior compared to other classifications.